2015
DOI: 10.1021/acs.inorgchem.5b00102
|View full text |Cite
|
Sign up to set email alerts
|

Structural Origin of the Anisotropic and Isotropic Thermal Expansion of K2NiF4-Type LaSrAlO4 and Sr2TiO4

Abstract: K2NiF4-type LaSrAlO4 and Sr2TiO4 exhibit anisotropic and isotropic thermal expansion, respectively; however, their structural origin is unknown. To address this unresolved issue, the crystal structure and thermal expansion of LaSrAlO4 and Sr2TiO4 have been investigated through high-temperature neutron and synchrotron X-ray powder diffraction experiments and ab initio electronic calculations. The thermal expansion coefficient (TEC) along the c-axis (αc) being higher than that along the a-axis (αa) of LaSrAlO4 [… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
15
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 60 publications
6
15
2
Order By: Relevance
“…The structural relaxation was performed in the primitive body-centered tetragonal unit cell, until the maximum residual forces on each atom were less than 6x10 -6 Ha/Bohr and the pressure was less than 2x10 -8 Ha/Bohr 3 . From our DFT calculations with the LDA exchange-correlation functional, we find lattice parameters a = 3.8217 Å and c = 12.3145 Å, which are about 2 % lower than our experimental results and prior results in the literature 49,51 . In contrast, our c/a ratios are almost the same (c/a = 3.2223 in DFT against c/a = 3.241 in our experiments and 3.241 49 , 3.247 51 in prior experiments).…”
Section: Computational Detailscontrasting
confidence: 73%
See 2 more Smart Citations
“…The structural relaxation was performed in the primitive body-centered tetragonal unit cell, until the maximum residual forces on each atom were less than 6x10 -6 Ha/Bohr and the pressure was less than 2x10 -8 Ha/Bohr 3 . From our DFT calculations with the LDA exchange-correlation functional, we find lattice parameters a = 3.8217 Å and c = 12.3145 Å, which are about 2 % lower than our experimental results and prior results in the literature 49,51 . In contrast, our c/a ratios are almost the same (c/a = 3.2223 in DFT against c/a = 3.241 in our experiments and 3.241 49 , 3.247 51 in prior experiments).…”
Section: Computational Detailscontrasting
confidence: 73%
“…From our DFT calculations with the LDA exchange-correlation functional, we find lattice parameters a = 3.8217 Å and c = 12.3145 Å, which are about 2 % lower than our experimental results and prior results in the literature 49,51 . In contrast, our c/a ratios are almost the same (c/a = 3.2223 in DFT against c/a = 3.241 in our experiments and 3.241 49 , 3.247 51 in prior experiments). Our results agree well with prior LDA calculations performed by Fennie and Rabe.…”
Section: Computational Detailscontrasting
confidence: 73%
See 1 more Smart Citation
“…An earlier synchrotron XRD measurement by Kawamura et al has shown a similar difference in the LaSrAlO 4 Ruddlesden-Popper material, where the La-O electronic interaction is stronger than the Sr-O electronic interaction. 62 Quantitatively, the calculated La-O electron density overlap in LaAlO 3 was weaker than the one observed from the experiments. Such differences between the computational and experimental results have been reported in the literature, e.g.…”
Section: Resultsmentioning
confidence: 65%
“…This Extended Module Materials Assembly (EMMA) method 10 was employed to aid in the determination of the structure of a large layered perovskite, Y 2. 24 21 , where the modular approach worked well to impose chemically sensible co-ordination chemistry on all of the atoms.…”
Section: Introductionmentioning
confidence: 99%